1983
DOI: 10.1128/aem.46.5.1182-1186.1983
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of 2,4,5-trichlorophenoxyacetic acid and chlorophenol metabolism in Pseudomonas cepacia AC1100

Abstract: The expression of the degradative genes encoding 2,4,5-trichlorophenoxyacetic acid (2,4,5-T), 2,4,5-trichlorophenol (2,4,5-TCP), and pentachlorophenol (PCP) dechlorination in a 2,4,5-T-degrading strain of Pseudomonas cepacia was examined during growth on alternate carbon sources. The dechlorination mechanisms for all three compounds were expressed in 2,4,5-Tand 2,4,5-TCP-grown cells but were not expressed in cells grown on succinate, glucose, or lactate. The addition of 2,4,5-TCP or PCP to cells grown on succi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
2

Year Published

1984
1984
1998
1998

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 9 publications
2
25
0
2
Order By: Relevance
“…In recent years, there has been considerable interest in using B. cepacia as a biocontrol agent because of its ability to antagonize and repress soil-borne plant pathogens (Janisiewicz and Roitman 1988). Other biotypes of B. cepacia have been implicated in human diseases (Thomassen et al 1985), plant disease (Burkholder 1950) and biodegration of pesticides (Karns et al 1983). Various factors responsible for the antagonistic properties of B. cepacia have been suggested (Weller 1988).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been considerable interest in using B. cepacia as a biocontrol agent because of its ability to antagonize and repress soil-borne plant pathogens (Janisiewicz and Roitman 1988). Other biotypes of B. cepacia have been implicated in human diseases (Thomassen et al 1985), plant disease (Burkholder 1950) and biodegration of pesticides (Karns et al 1983). Various factors responsible for the antagonistic properties of B. cepacia have been suggested (Weller 1988).…”
Section: Discussionmentioning
confidence: 99%
“…From this mixed culture, Kilbane et al [170] isolated a pure culture of Pseudomonas cepacia designated strain ACll00 that utilized 2,4,5-T as a sole source of carbon and energy. The bacterium degraded 2,4,5-T via 2,4,5-trichlorophenol with essentially 100% release of chloride [47,170,171]. Resting cells of 2,4,5-T-grown P. cepacia strain AC1100 were also able to degrade several other polychlorinated phenols, including pentachlorophenol [47].…”
Section: Aerobic Degradation Of Chlorophenoxyalkanoic Acidsmentioning
confidence: 99%
“…Resting cells of 2,4,5-T-grown P. cepacia strain AC1100 were also able to degrade several other polychlorinated phenols, including pentachlorophenol [47]. Conversion of 2,4,5-T was constitutively expressed, while degradation of chlorophenols was induced by 2,4,5-trichlorophenol [171]. Sangodkar et al [61] showed that 2,4,5-trichlorophenol was subsequently degraded via hydroxylation and dechlorination to 2,5-dichloro-para-hydroquinone and dechlorinated further to 5-chloro-l,2,4-trihydroxybenzene ( Fig.…”
Section: Aerobic Degradation Of Chlorophenoxyalkanoic Acidsmentioning
confidence: 99%
“…P C P is quite susceptible to photolysis [4] but is little affected by oxidation, hydrolysis or volatilization [ 5 ] . Biodegradation can be significant [6,7] but not in all circumstances [8]. Sorption is also a variable phenomenon, apparently occurring in acidic soils in proportion to organic content [5,6,9].…”
Section: Introductionmentioning
confidence: 99%